Analgesic Efficacy of Thoracoscopic Direct-View Versus Ultrasound-Guided Thoracic Paravertebral Block in Multi-Port Video-Assisted Thoracoscopic Lung Surgery: A Randomized Controlled Non-Inferiority Study - Tong Y; Wu J; Wu X; Mo Y; Wang F (Drug Design, Development and Therapy)
Yao Tong,1,* Jimin Wu,2,* Xuhui Wu,3 Yunchang Mo,1 Faxing Wang2,4 1Department of Anesthesiology, the First Affiliated Hospital of Wenzhou Medical University, Wenzhou, People’s Republic of China; 2Department of Anesthesiology, Lishui People’s Hospital, Lishui Hospital of Wenzhou Medical University, Lishui, People’s Republic of China; 3Department of Thoracic Surgery, Lishui People’s Hospital, Lishui Hospital of Wenzhou Medical University, Lishui, People’s Republic of China; 4Oujiang Laboratory (Zhejiang Lab for Regenerative Medicine, Vision and Brain Health), Wenzhou Medical University, Wenzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Faxing Wang, Department of Anesthesiology, Lishui People’s Hospital, Lishui Hospital of Wenzhou Medical University, No. 15, Dazhong Street, Lishui, Zhejiang Province, 323000, People’s Republic of China, Email wfx2023@wmu.edu.cn Yunchang Mo, Department of Anesthesiology, the First Affiliated Hospital of Wenzhou Medical University, Shangcai Village, Nanbaixiang Street, Ouhai District, Wenzhou, Zhejiang, 325000, People’s Republic of China, Email myc1104@wmu.edu.cnPurpose: This study compares the analgesic effects of the Thoracoscopic Direct-view Thoracic Paravertebral Nerve Block (DTPVB) with those of the Ultrasound-guided Thoracic Paravertebral Nerve Block (UTPVB), providing a clinical reference.Patients and Methods: Sixty-eight patients undergoing three-port video-assisted thoracic surgery (VATS) with general anesthesia were randomly assigned to either the DTPVB group (Group D, n = 34) or the UTPVB group (Group U, n = 34). Both groups received a 10 mL injection of 0.75% ropivacaine at the T4 and T7 interspaces. Primary outcomes were cumulative sufentanil equivalents from the start of lung manipulation to 24 hours postoperatively, with group differences assessed against a non-inferiority margin of 5 μg (Δ). Secondary outcomes include postoperative pain scores, analgesic consumption, patient satisfaction, adverse effects, and other related indicators.Results: The cumulative use of sufentanil equivalents from the start of lung manipulation to 24 hours postoperatively was 35.0 ± 6.1 μg in Group D and 33.2 ± 5.6 μg in Group U, with no significant difference (P = 0.217). The difference in cumulative sufentanil equivalents (Group D minus Group U) was 1.8 (95% CI − 1.07, 4.65), within the non-inferiority margin of 5 (Δ). Postoperative pain scores, analgesic consumption, adverse effects, and complications were similar were similar between groups. However, DTPVB was associated with lower anxiety and higher satisfaction (P< 0.001). At 15 minutes post-block, ropivacaine plasma concentrations were higher in Group D (P=0.024).Conclusion: DTPVB, via transmural pleural puncture, was non-inferior to UTPVB in analgesic efficacy from the beginning of the manipulation of the lungs in operation to 24h postoperatively. DTPVB provides a good alternative, especially for patients who are anxious before surgery, have difficulty cooperating with UTPVB, or in cases where UTPVB puncture fails. However, when using high concentrations of ropivacaine, greater vigilance for toxicity is required.Keywords: thoracic paravertebral block, TPVB, video-assisted thoracoscopic surgery, VATS, pain management